2021
DOI: 10.1111/ans.17388
|View full text |Cite
|
Sign up to set email alerts
|

Clinical utility of stimulated cholescintigraphy using a standardized Ensure‐Plus fatty meal protocol in patients with suspected functional gallbladder disorder: a retrospective study of seven‐years clinical experience

Abstract: Background The clinical utility of fatty meal stimulated cholescintigraphy particularly using a standardized formulation in patients with suspected functional gallbladder disorder has not been extensively studied. We present our seven‐year clinical experience using an Ensure plus protocol. Methods A retrospective study was performed on patients undergoing stimulated cholescintigraphy using Ensure Plus for evaluation of suspected functional gallbladder disorder. A gallbladder ejection fraction (GBEF) of <33% wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Initial work on gallbladder contraction and biliary excretion resulted from cholegraphic studies in which patients were administered an oral cholecystagogue (22)(23)(24)(25). Examples of the reported oral cholecystagogues include milk, corn oil emulsion, Cholex (egg yolk, soya lecithin, glycerin, and peanut oil), D-sorbitol solution, safflower oil emulsion, vegetable oil, fatty meal (Lipomul), and Ensure Plus (5,8,12,22,23,(25)(26)(27)(28)(29)(30)(31)(32)(33). In 1957, cholecystokinin was developed as an intravenous cholecystagogue demonstrating prompt and strong contraction of the gallbladder and opening of the sphincter of Oddi (2,3).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Initial work on gallbladder contraction and biliary excretion resulted from cholegraphic studies in which patients were administered an oral cholecystagogue (22)(23)(24)(25). Examples of the reported oral cholecystagogues include milk, corn oil emulsion, Cholex (egg yolk, soya lecithin, glycerin, and peanut oil), D-sorbitol solution, safflower oil emulsion, vegetable oil, fatty meal (Lipomul), and Ensure Plus (5,8,12,22,23,(25)(26)(27)(28)(29)(30)(31)(32)(33). In 1957, cholecystokinin was developed as an intravenous cholecystagogue demonstrating prompt and strong contraction of the gallbladder and opening of the sphincter of Oddi (2,3).…”
Section: Introductionmentioning
confidence: 99%
“…The descriptive statistics from that same study found that the sensitivity, specificity, positive predictive value, and negative predictive value for chronic cholecystitis on histopathology or for a subjective reduction in postoperative biliary-type pain in patients undergoing cholecystectomy. Li et al assessed the symptoms for patients undergoing hepatobiliary scintigraphy with Ensure Plus for suspected chronic functional gallbladder disorder, comparing the symptom outcomes after cholecystectomy or conservative management in patients with normal or abnormal gallbladder ejection fractions (27). In patients with abnormal gallbladder ejection fractions on Ensure Plus hepatobiliary scintigraphy, 97% experienced symptom improvement after cholecystectomy, compared with 65% who were treated conservatively.…”
Section: Introductionmentioning
confidence: 99%
“…Historically, cholecystokinin analogs such as sincalide have been used; however, because these analogs are often subject to supply shortages, alternative cholecystagogues have been evaluated (4,5). A well-studied oral cholecystagogue is Ensure Plus (Abbott Laboratories), a liquid fatty meal (6)(7)(8). Ensure Plus is readily available, inexpensive, and effective in assessing gallbladder ejection fraction.…”
mentioning
confidence: 99%